AB1132 Higher rates of obesity and associations with poorer clinical status in patients with RA, OA and SLE: a cross-sectional study from routine care. (15th June 2017) - Castrejon, I; Shakoor, N; Block, JA; Pincus, T
Abstract : Background: Obesity is a risk factor for many chronic rheumatic diseases. In rheumatoid arthritis (RA), obesity is associated with increased comorbidities, higher medical costs, disease activity, and poorer physical function 1 . In OA, obesity is a risk factor for both incidence and progression, and has a negative impact on outcomes 2 . In systemic lupus erythematous (SLE), obesity is associated with more severe renal involvement, lower quality of life, and increased cardiovascular risk 3 . Objectives: To assess associations of obesity with patient self-report multidimensional health assessment questionnaire (MDHAQ) scores and physician global assessments in patients with RA, OA and SLE seen in routine care. Methods: All patients at one academic center complete a MDHAQ, which includes a 0–10 scale for physical function (FN), 0–10 visual analogue scales (VAS) for pain (PN) and patient global assessment (PATGL), compiled into a 0–30 RAPID3, as well as scales for fatigue, depression, and demographic data. Physicians complete a VAS for patient global (DOCGL). Body Mass Index (BMI) was calculated from the medical record as weight (kg)/ height (meters) 2 . Patients were classified by BMI as normal (18.5–25), overweight (25–30), or obese (>30) according to the WHO guidelines. Demographic and clinical MDHAQ data were compared in the 3 diagnostic groups according to BMI groups using ANOVA and chi-square tests. Results: 396 patients with RA, 425 with OA, and 306 with SLE were studied. Obesity was reported by 40% of RA and SLE patients, and 59% of OA patients, a higher percentage than matched individuals in the general population in the same region (30.8%). Obesity was higher in African-American patients (48% in RA, 70% in OA, and 53% in SLE). Education level, gender, and age did not differ significantly across the groups. Obesity was associated with poorer physical function, poorer patient global and higher pain in all 3 diagnostic groups, with higher depression scores in OA and SLE (Table). DOCGL was significantly higher only in OA (data not shown). Conclusions: Obesity is more prevalent in patients with rheumatic diseases compared with the general population. Obese patients had poorer status on most MDHAQ scores, particularly physical function and pain. Obesity is an important comorbidity in patients with rheumatic diseases. References: J Rheumatol 2015, 42(12):2261–2269. Obes Rev 2014, 15(7):578–586. Autoimmunity Reviews 2014;13: 981–1000. Disclosure of Interest: I. Castrejon: None declared, N. Shakoor: None declared, J. Block: None declared, T. Pincus Shareholder of: Health Report Services, Inc